Digital applications: the future in psychiatry? - Thibaut, Florence (Dialogues Clin Neurosci, 2016)
Digital applications and new mobile technologies can change the nature of the psychiatrist-patient relationship and future clinical practice in terms of diagnosis, follow-up, and treatment, but need to be further studied. This issue explores these new approaches in psychiatry.